Identifikasi suhu permukaan darat (LST) menggunakan Multi-Temporal Citra SENTINEL 3 2019-2023 - Putri, Sri Kandi; Pertiwi, Mentari Dian; Arifian, Naf'an; Shatri, Alni; Septria, Adit; Aisyah, Juliana (Sustainability (STPP) Theory, Practice and Policy, 2024)
Land Surface Temperature (LST) is widely utilized in current studies, particularly as an initial survey tool to assess geothermal activity in locations suspected to have geothermal sources. The research method involves geometric correction of Sentinel-3 imagery and conversion of temperature units from Fahrenheit (F) to Celsius (C) to ensure accuracy in temperature measurement. Image data processing from Sentinel-3, including thermal band analysis, is carried out to generate land surface temperature values. The field-measured temperatures are then compared to the land surface temperature data obtained through processing. The temperatures in the location, ranging from 23°C to 35°C, fall within the minimum geothermal temperature range, indicating potential geothermal activity. However, the LST values from the image data exhibit some differences compared to the on-site measurements. These discrepancies are categorized into classes I (23.7 – 24°C), II (24 – 24.3°C), and III (24.3 – 24.8°C), marked by red areas in the LST values. These discrepancies are attributed to various factors during image recording and processing, such as atmospheric interference and sensor calibration.